Monetary valuation of the damage effects of water pollution on human health (the case of Subin, Sisa and Oda rivers in Kumasi) - Adu-Poku, Richard (2011)
A thesis submitted to the Department of Economics and Industrial Management, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Arts degree in economics.